An Experimental study: Effectiveness of Nursing protocol on postoperative outcome among patients undergoing major Visceral Surgeries in a Selected Tertiary Care Hospital at Delhi (International Journal of Nursing Education, 2023)
Introduction : Surgery is almost always viewed as a life crisis and evokes anxiety and fear . In line with the growingnumber of surgical procedures being performed worldwide, postoperative complications are also increasing,proportionately increasing mortality, impairing patients’ postoperative outcome, lengthening intensive care andtotal hospital stay. Preoperative assessment and care is extremely important prior to any invasive procedureincluding minor and major surgical procedures. Physical and psychological preparation tends to improve surgicaloutcomes. Preoperative teaching provides with pertinent information concerning the surgical process and theintended surgical procedure as well as anticipated patient behavior (anxiety, fear), expected sensation, and theprobable outcomes. The experimental study was conducted to assess the effectiveness of nursing protocol onpostoperative outcome among patients undergoing major visceral surgeries in a selected tertiary care hospital. Theobjectives of the study were to assess the post operative outcome of patients undergoing major visceral surgeriesin the study and control group, to determine the effectiveness of nursing protocol on postoperative outcomeamong patients undergoing major visceral surgeries and to associate the post operative outcome with the sociodemographic variables.Materials and Methods: An experimental, post-test only design was used to conduct the study at tertiary carehospital in Delhi. The intervention was carried out in the pre-operative surgical wards of the tertiary care hospitaland post-operative data was collected in the inpatient surgical unit. 63 samples in the experimental group and63 samples in the control group were selected by simple random sampling technique. The study revealed thatthere was a significant difference in the pain scores on the seventh day after surgery and on the patient satisfactionrelated to preoperative education and intraoperative care.
Keywords: Preoperative education, Postoperative, visceral surgery, nursing protocol, postoperative outcome.